Ferrous ammonium phosphate (FeNH4PO4) as a new food fortificant: Iron bioavailability compared to ferrous sulfate and ferric pyrophosphate from an instant milk drink - Walczyk, T. (2014)
10.1007/s00394-012-0445-y